The patronage of religious tourism seen from its motivations that predict satisfaction and loyalty: The Virgin of Chaguaya in Bolivia - Carvache-Franco, Mauricio; Loaiza-Torres, Jose; Carvache-Franco, Orly; Fernández-Cruz, José Eduardo; Carvache-Franco, Wilmer (PloS one, 2024)
This study focused on pilgrimages as part of religious tourism and aimed to achieve the following objectives: identify the main motivational factors of religious tourism focused on pilgrimages; analyze the motivational dimensions that predict satisfaction in religious tourism focused on pilgrimages; analyze the motivational dimensions that predict loyalty in religious tourism focused on pilgrimages. The study was conducted during the pilgrimage to the Virgin of Chaguaya in Bolivia. The sample consisted of 384 tourists who were surveyed on-site. The statistical techniques used included factor analysis and multiple regression. The results revealed four motivational dimensions: Tourism and Escape, Religious Experience, Belief Experience, and Shopping. Additionally, specific motivations that influence the satisfaction and loyalty of attendees at religious events such as pilgrimages have been identified, among them the "Religious Experience" and the "Belief Experience" motivational dimensions. The findings will contribute to planning and management guidelines for religious event administrators and provide information to academic literature.